LITHIC TECHNOLOGY AND ETHNOARCHAEOLOGY: A CRITICAL ANALYSIS OF THE INTERPRETATIVE POSSIBILITIES OF MATERIAL CULTURE - Coutinho , Hebert Rogério do Nascimento; da Rocha, Luiz Carlos Medeiros; da Silva, Abrahão Sanderson Nunes Fernandes (Seven Editora, 2025)
The critical analysis presented here has as its analytical object the interpretative possibilities stemming from the Anthropology of Technique and Technology and its relationship with the foundations of Agency in material culture studies. To this end, we have posed the following question as a problem: which elements of material culture, especially of a lithic nature, make it possible to interpret aspects outside of material causality? From this perspective, as far as the theoretical apparatus is concerned, we took a processual approach, perceiving the technique as permeated by possible practices and logics of use. In addition, we engage in critical reflection in order to identify elements that help to overcome the methodological dichotomy of Man/Nature, so that the problem listed here can be resolved. In addition, we used ethnoarchaeological precepts in order to point out solutions for the realization of the analytical proposal demonstrated in this article. DOI: https://doi.org/10.56238/sevened2025.021-073